Analisis “Lihat Sekitar” Buku Ajar untuk Kelas IV SD/MI Bab 4 (Meliuk dan Menerjang) Tahun 2023 Berbasis Kelayakan Buku BSNP - Nayla Rachma Putri Widyasari; Panca Dewi Purwati; Elya Anggita Dewi; Aulia Nawa Wulandari; Irma Ayu Diana; Alya Bunga Aura (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Textbooks play an important role in the learning process because they are the main source for students and teachers in achieving the set learning outcomes (CP). However, the suitability of the contents of the textbooks needs to be reviewed to ensure their compliance with national education standards. This study aims to (1) analyze the suitability of the contents of Chapter 4 of the Indonesian Language textbook for grade IV SD/MI based on elements and learning outcomes; (2) evaluate the accuracy and novelty of the material; (3) examine the use of language in delivering the material; and (4) assess the presentation and graphical appearance of the book according to BSNP standards. This study uses a content analysis method with an assessment instrument based on the textbook suitability indicators according to the National Education Standards Agency (BSNP). The object of the study is the Indonesian Language textbook for grade IV SD/MI entitled "lihat Sekitar untuk SD/MI Kelas IV (Revised Edition)" by Eva Nukman and Cicilia Erni Setyowati, especially Chapter IV entitled "Meliuk dan Menerjang". The results of the analysis show that the quality of the book's contents is classified as appropriate and actual, with material that is relevant to the cultural and social context of students. From the language aspect, the book uses correct spelling and language that is straightforward and easy to understand. The presentation of the material is able to arouse students' learning motivation and is equipped with practice questions at the end of the chapter. The quality of the graphics is considered very good with informative illustrations that support students' understanding. The conclusion of this study is that the book is suitable for use in learning with some minor improvements to spelling. It is recommended that authors and publishers pay more attention to punctuation consistency and include exercises that encourage student activity more evenly in each sub-chapter.